LATIHAN ZIG-ZAG RUN LEBIH BERPENGARUH DARI PADA LATIHAN HEXAGON DRILL TERHADAP AGILITY - Annisa Adenikheir; Yelva Febriani (Universitas Fort de Kock Bukittinggi, 2022)
Agility is an activity of moving motion from one side to another so that the movement pattern can move around and can affect daily activities. In girls aged 10-12 years, agility is important because during this period hormonal and metabolic changes can affect the level of agility in girls aged 10-12 years. Zig-Zug Run and Hexagon Drill exercises can increase agility. This research design is quasi experimental with a two group pretest-posttest design approach. This research was conducted for 3 weeks in July 2020 on 22 girls aged 10-12 years with 11 people in the Zig-zag Run group and 11 people in the Hexagon Drill group. The collected data is processed and analyzed computerized. The results showed an increase in the average agility level of respondents in the hexagon drill group was 1.27 and an increase in the average agility level of respondents in the Zig-zag run group was 2.18 and p value = 0.001 where there was an increase in the hexagon drill group d. rill and zigzag run exercises. The conclusion of this study is that the zig zag run exercise is more effective in increasing the agility of girls aged 10-12 years. Keyword : Zig-zag Run, Hexagon Drill, Agility